Consensus on maturity-related injury risks and prevention in youth soccer: A Delphi study. - Joseph Sullivan; Simon Roberts; Kevin Enright; Martin Littlewood; David Johnson; David Hartley (PLoS ONE, 2024)
The aim of this study was to achieve consensus from leading sport and exercise science practitioners in professional soccer academies surrounding (i) motivations for maturity-related data collection (ii) maturity-related injury risk factors (iii) how maturity-related data informs injury prevention practices and (iv) the use of bio-banding as an alternative injury prevention strategy. The study adopted an iterative three round online Delphi method, where a series of statements were rated by expert panellists. Consensus agreement was set at ≥70% for all statements. Nine panellists participated in all three rounds (69% response rate). Consensus was achieved for a total of sixteen statements. Panellists agreed that the period during and 12-months post peak height velocity, muscle strength/flexibility imbalances and maturity status (% predicted adult height) as the most important maturity-related injury risk factors. Panellists also agreed that maturity-related data collection is important for injury prevention as well as physical and performance-related purposes, but not for recruitment or retain/release purposes. It was also evident that variability and misunderstanding of key language terms used within the growth and maturation literature exists. It was agreed that practitioners who are responsible for conducting maturational assessments require additional training/education to enhance their application, delivery and outcomes. The findings indicate that maturity-related data collection is part of a multidisciplinary process, dedicated towards the long-term development of players. Greater training and education are required along with increased dissemination of research findings surrounding the full uses for bio-banding. This study provides guidance on maturity-related injury risks and prevention in youth soccer for practitioners.